Pengaruh Kualitas Produk, Fitur Produk dan Promosi Terhadap Keputusan Pembelian Daihatsu Gran Max dengan Brand Image Sebagai Variabel Moderasi - Muharom, Mumuh; Yulia, Iis Anisa; Mulia, Agus Prana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze the influence of product quality, product features and promotion on purchasing decisions for the Daihatsu Gran Max with brand image as a moderating variable. The sample used in this research was 200 respondents. Data was collected using a purposive sampling method and hypothesis testing using Moderated Regression Analysis (MRA). The results of this research show that Product Quality has a significant influence on Purchasing Decisions, Product Features have a significant influence on Purchasing Decisions and Promotion has a significant influence on Purchasing Decisions, Brand Image can moderate the influence of Product Quality, Product Features and Promotion on Purchasing Decisions.